2002
DOI: 10.1016/s0736-0266(02)00045-1
|View full text |Cite
|
Sign up to set email alerts
|

Selective joint denervation promotes knee osteoarthritis in the aging rat

Abstract: Osteoarthritis is the most common joint disorder with aging, but its cause is unknown. Mice lose joint afferents with aging, and this loss precedes development of osteoarthritis. We hypothesized a loss of joint afferents is involved in the pathogenesis of osteoarthritis.To test this hypothesis, we denervated knee joints of 16 rats at age 2 months, by intra-articular injection o f an immunotoxin. The imrnunotoxin killed neurons after retrograde axonal transport to the cell body. At 16 or 24 months follow-up, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 32 publications
1
42
0
1
Order By: Relevance
“…(3) Finally, is there a correlation between age and mechanoreceptor density? This has been reported in the literature in other joints [22,[36][37][38]. If a similar correlation is found, it may provide insight into the effect of age and severity progression of OA.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…(3) Finally, is there a correlation between age and mechanoreceptor density? This has been reported in the literature in other joints [22,[36][37][38]. If a similar correlation is found, it may provide insight into the effect of age and severity progression of OA.…”
Section: Introductionsupporting
confidence: 81%
“…Other studies have suggested an age-related decrease of mechanoreceptors and consequently impaired proprioceptive traits [23,40,44]. Previous studies have also established a correlation between age and mechanoreceptor density [22,[36][37][38]. To date, underlying pathophysiological mechanisms of age-related changes of proprioception have not been fully delineated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that neurogenic muscular atrophy is directly due to OA of the knee, since there are no reports in the literature of structural changes of the peripheral nerves as direct consequence of OA. It does seem conceivable, however, that denervation or reinnervation processes had already started before or soon after the initial clinical manifestation of OA, as evidenced by findings reported by Salo et al (41). In their study, experimentally induced loss of joint afferents in rats led on average to a 54% higher score of histologic severity of OA compared with control knees.…”
Section: Discussionmentioning
confidence: 74%
“…However, considerable more investigation is needed to provide clarity with regard to the dynamic aspects of their role(s), and how neural elements are modulated by genetics, aging, and sex and co-morbidities. Some of this complexity likely serves fundamental roles in repair and restoration of function, but it is clear also from the work of Salo et al (33,34,198) that innervation of normal joint tissues can decline with age in both rats and mice, and thus elevate risk for degenerative joint disease. Whether similar changes occur in tendons and ligaments throughout the body during aging and following events such as menopause, remains to be delineated.…”
Section: Perspectivementioning
confidence: 99%